2018
DOI: 10.2478/pomr-2018-0065
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach of Coastal Cliff Monitoring using Mobile Laser Scanning

Abstract: The article proposes a new approach of coastal cliff monitoring which bases on a new comprehensive monitoring system, being a combination of mobile scanning from the sea with the geotechnical stability analysis. Mobile laser scanning is an innovative solution for 3D data collection which allows the monitored object geometry to be precisely measured, thus providing opportunities for series of analyses contributing to the development of an improved monitoring system. The authors present selected cliff profiles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…They used a boat-based MMS to scan 3D point clouds of unstable coastal cliffs to detect rockfalls and erosional deposits. A similar case is proposed by [12] who described a new approach of coastal cliff monitoring, in Poland, which is based on a combination of MLS from the sea with the geotechnical stability calculations. A 3D mapping was carried out by an airborne MMS, installed on a helicopter, to monitor a small landslide in the North Yorkshire coast in the UK.…”
Section: Related Workmentioning
confidence: 96%
“…They used a boat-based MMS to scan 3D point clouds of unstable coastal cliffs to detect rockfalls and erosional deposits. A similar case is proposed by [12] who described a new approach of coastal cliff monitoring, in Poland, which is based on a combination of MLS from the sea with the geotechnical stability calculations. A 3D mapping was carried out by an airborne MMS, installed on a helicopter, to monitor a small landslide in the North Yorkshire coast in the UK.…”
Section: Related Workmentioning
confidence: 96%
“…Aerial surveys are generally performed by Unmanned Aerial Vehicles (UAVs) and mainly used for beach surveys [1][2][3], whereas data collected from a terrestrial point of view are more suited to cliff surveys, allowing for better capturing the cliff face. These terrestrial data are typically obtained using a Terrestrial Laser Scanner (TLS) [4,5], a Mobile Laser Scanner (MLS) [6,7], or terrestrial photogrammetry [8,9]. This article focuses more particularly on these terrestrial methods.…”
Section: Introductionmentioning
confidence: 99%
“…The chosen cliff cross-section was modeled using an elasto-plastic model with the classical Mohr-Coulomb yield criterion. The Factor of Safety (FS) for Mohr-Coulomb material with the Shear Strength Reduction (SSR) method [64,65] was calculated using Equation (4):…”
Section: Stability Analysis Methodsmentioning
confidence: 99%
“…This is an important issue in three geotechnical respects: (1) the uncertainty in the values from archival investigations [11,48] (c.f. the authors in Reference [65] used slightly different parameters that were obtained from another source); (2) the complicated geology and possible variability in the parameters in the soil profile; and (3) the fact that water can change the values of soil parameters (e.g., it can lower cohesion). The analysis showed that, for the initial case (no elevation in the water table), the most sensitive parameters were the friction angle and the cohesion in the bottom layer (the clay from which the cliff is built).…”
Section: Calculated Factor Of Safety (Fs)mentioning
confidence: 99%